Prosthetic valve endocarditis caused by Pseudomonas aeruginosa with variable antibacterial resistance profiles: a diagnostic challenge - Nicolas Gürtler; Michael Osthoff; Florian Rueter; Daniel Wüthrich; Lukas Zimmerli; Adrian Egli; Stefano Bassetti (BMC Infectious Diseases, 2019)
Abstract Background Infective endocarditis (IE) caused by gram-negative bacilli is rare. However, the incidence of this severe infection is rising because of the increasing number of persons at risk, such as patients with immunosuppression or with cardiac implantable devices and prosthetic valves. The diagnosis of IE is often difficult, particularly when microorganisms such as Pseudomonas aeruginosa, which rarely cause this infection, are involved. One of the mainstays for the diagnosis of IE are persistently positive blood cultures with the same bacteria, while polymicrobial bacteremia usually points to another cause, e.g. an abscess. The antimicrobial resistance profile of some P. aeruginosa strains may change, falsely suggesting an infection with several strains, thus further increasing the diagnostic difficulties. Case presentation A 66-year old male patient who had a transcatheter aortic valve implantation (TAVI) one year previously developed fever seven days after an elective inguinal hernia repair. During the following four weeks, P. aeruginosa with different antibiotic resistance profiles was repeatedly isolated from blood cultures. Repeated trans-esophageal echocardiograms (TEE) were negative and an infection by different P. aeruginosa strains was suspected. Extensive diagnostic workup for an infectious focus was performed with no results. Finally, an oscillating mass on the aortic valve was detected by TEE five weeks after the initial positive blood cultures. P. aeruginosa endocarditis was confirmed by culture of the surgically removed valve. Whole genome sequencing of the last two P. aeruginosa isolates (valve and blood culture) revealed identical strains, with genome mutations for AmpR, AmpD and OprD. Conclusions The diagnosis of prosthetic valve endocarditis is particularly difficult for several reasons. The modified Duke criteria have a lower sensitivity for patients with prosthetic valve endocarditis and the infection may be caused by “unusual” pathogens such as P. aeruginosa. Patients with repeatedly positive blood cultures should make clinicians suspicious for endocarditis even if imaging studies are negative and if isolated pathogens are “unusual”. Repeatedly positive blood cultures for P. aeruginosa should be considered as “persistent bacteremia” (suspicious for IE) even in the presence of different antibiotic susceptibility patterns, since P. aeruginosa might rapidly activate or deactivate resistance mechanisms depending on antibiotic exposition.